Pendapatan dan Efisiensi Usahatani secara Finansial Varietas Padi Bk Situbondo 01 Agritan di Desa Battal Kabupaten Situbondo - Agus Supriono; Rofiu Sisil Annisa; Tiffany Rahma Abdillah; Rizky Yanuarti; Julian Adam Ridjal; Cindera Rosa Damascena (Lembaga Pengembangan Kinerja Dosen, 2025)
In line with this national rice productivity improvement strategy, the Situbondo Regency Government in East Java Province is actively participating in initiating the development of new superior rice varieties. In early 2023, Situbondo Regency released a new superior rice variety, the Bk Situbondo 01 Agritan Variety. This new rice variety was developed for the IP 400 program. In 2024, the cultivation of this superior rice variety, Bk Situbondo 01 Agritan, began in several villages, one of which was in Battal Village, Panji District, primarily by the Joyo Mulyo 3 Farmers Group. In this regard, it is deemed necessary to conduct research to determine the income and financial efficiency of the superior rice variety Bk Situbondo 01 Agritan. The results of the study indicate that financially the income is recorded as profitable and the farming is efficient. Financially, if it is calculated that there is a decrease in the amount of production and a decrease in production prices of up to 15%, as well as an increase in variable costs of up to 15%, assuming that other factors are considered constant, the new superior rice variety farming business Bk Situbondo 01 Agritan, recorded that the income is still profitable and the farming business is still efficient. It can also be seen that the factors: (a) decrease in the amount (quantity) of production, and (b) decrease in production prices, are relatively more sensitive in responding to the decrease in the level of income and efficiency of the farming business, when compared to the factor: (c) increase in variable costs of the farming business.